Alterations in sialic-acid O-acetylation glycoforms during murine erythrocyte development. (7th January 2019) - Mahajan, Vinay S; Alsufyani, Faisal; Mattoo, Hamid; Rosenberg, Ian; Pillai, Shiv
Abstract: We used Casd1 -deficient mice to confirm that this enzyme is responsible for 9- O -acetylation of sialic acids in vivo . We observed a complete loss of 9- O -acetylation of sialic acid on the surface of myeloid, erythroid and CD4 + T cells in Casd1 -deficient mice. Although 9- O -acetylation of sialic acids on multiple hematopoietic lineages was lost, there were no obvious defects in hematopoiesis. Interestingly, erythrocytes from Casd1 -deficient mice also lost reactivity to TER-119, a rat monoclonal antibody that is widely used to mark the murine erythroid lineage. The sialic acid glyco-epitope recognized by TER-119 on erythrocytes was sensitive to the sialic acid O -acetyl esterase activity of the hemagglutinin-esterase from bovine coronavirus but not to the corresponding enzyme from the influenza C virus. During erythrocyte development, TER-119 + Ery-A and Ery-B cells could be stained by catalytically inactive bovine coronavirus hemagglutinin-esterase but not by the inactive influenza C hemagglutinin-esterase, while TER-119 + Ery-C cells and mature erythrocytes were recognized by both virolectins. Although the structure of the sialoglycoconjugate recognized by TER-119 was not chemically demonstrated, its selective binding to virolectins suggests that it may be comprised of a 7, 9-di- O -acetyl form of sialic acid. As erythrocytes mature, the surfaces of Ery-C cells and mature erythrocytes also acquire an additional distinct CASD1-dependent 9- O -acetyl sialic acid moiety that can be recognized by virolectins from both influenza C and bovine coronavirus.